2021
DOI: 10.3390/cancers13225772
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status as a Predictive Biomarker for Immunotherapy Outcomes in Advanced Head and Neck Cancer

Abstract: The association between pretreatment nutritional status and immunotherapy response in patients with advanced head and neck cancer is unclear. We retrospectively analyzed a cohort of 99 patients who underwent treatment with anti-PD-1 or anti-CTLA-4 antibodies (or both) for stage IV HNSCC between 2014 and 2020 at the Johns Hopkins Hospital. Patient demographics and clinical characteristics were retrieved from electronic medical records. Baseline prognostic nutritional index (PNI) scores and pretreatment body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Moreover, albumin decrease has been shown to be associated with rapid clearance of pembrolizumab in advanced cancer [ 31 ]. Second, the GNRI incorporates ideal weight into its calculation, which better resembles dynamic changes in chronic diseases such as tumor cachexia [ 26 , 27 , 32 ]. For example, Johannet et al showed that malnutrition, defined as weight loss six months prior to treatment, had a negative impact on immunotherapy response in non-small cell lung cancer, while baseline BMI did not [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, albumin decrease has been shown to be associated with rapid clearance of pembrolizumab in advanced cancer [ 31 ]. Second, the GNRI incorporates ideal weight into its calculation, which better resembles dynamic changes in chronic diseases such as tumor cachexia [ 26 , 27 , 32 ]. For example, Johannet et al showed that malnutrition, defined as weight loss six months prior to treatment, had a negative impact on immunotherapy response in non-small cell lung cancer, while baseline BMI did not [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadwell et al found that in elderly cancer patients, PNI was associated with 6-month postoperative mortality ( 33 ). In addition, the PNI can be combined with the neutrophil/lymphocyte ratio (NLR), and lactate dehydrogenase (LDH) to synergistically assess PFS and OS in patients with advanced cancer, receiving immunotherapy ( 34 , 35 ). It has also been reported that the PNI has a significant association with prognosis in patients undergoing surgery and who have digestive system tumors, such as liver and gastric cancer ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early, late, and no nutritional counselling resulted in a 1-year OS rate of 95.0, 87.5, and 81.3% ( P = 0.035) in 243 locally advanced-HNSCC patients scheduled for chemoradiation [67]. Another retrospective study suggested a correlation between baseline prognostic nutritional index and OS and PFS (OS: HR: 0.464;95% CI: 0.26–50.814; P = 0.007 and PFS: HR: 0.525;95% CI: 0.341–0.808; P = 0.003 in HNSCC patients receiving immunotherapy [68]. An Italian study will evaluate the efficacy of immunotnutrition to improve tolerance to chemoradiation in locally advanced-HNSCC and is currently ongoing (NCT04611113) [69].…”
Section: Improving Tolerability: Special Considerationsmentioning
confidence: 99%